ANALISIS MINAT BELAJAR MATEMATIKA SISWA BERDASARKAN GENDER DI MTsN 5 AGAM - Devi Sonia Wati; Gema Hista Medika; Rita Eka Fitri (Universitas Pahlawan Tuanku Tambusai, 2022)
Interest is a very important element for the success of student learning. Male and female students also have differences in paying attention to the learning process. Not only that, in terms of interest in learning mathematics, male and female students also have differences. Discipline in learning mathematics for male students and female students also sees differences. This research is a qualitative research. The instrument of this study were observation and questionnaires. The questionnaire used in this study was a questionnaire about students interest in learning mathematics. This research was conducted because there were differences between male students and female students interest in learning mathematics. The research was conducted to find out the interest in learning mathematics for Madrasah Tsanawiyah student based on gender. This research was conducted atMTsN 5 Agam. The population of this study were students of class VIII MTsN 5 Agam in 8 classes. Sampling of this research by urosive sampling technique. The subjects of this study were 27 students in class VIII-H MTsN 5 Agam, consisting of 10 male students and 17 female students. The result of this study showed that the percentage of the result of the questionnaire answered by female students was 59,64%, which means that most female students have an interest in learning mathematics. And male student have a percentage of 55,75% meaning that most male students are interested in learning mathematics. Keywords : Interest in learning, learning mathematics.